2013
DOI: 10.3310/hta17150
|View full text |Cite
|
Sign up to set email alerts
|

Randomised Assessment of Treatment using Panel Assay of Cardiac markers – Contemporary Biomarker Evaluation (RATPAC CBE)

Abstract: Reports are published in Health Technology Assessment (HTA) if (1) they have resulted from work for the HTA programme, and (2) they are of a sufficiently high scientific quality as assessed by the reviewers and editors.Reviews in Health Technology Assessment are termed 'systematic' when the account of the search appraisal and synthesis methods (to minimise biases and random errors) would, in theory, permit the replication of the review by others. HTA programmeThe HTA programme, part of the National Institute f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 274 publications
(209 reference statements)
1
35
0
Order By: Relevance
“…Furthermore, it may take more than 24 h to come back or it will have to be sent elsewhere to study this assay. These disadvantages of copeptin assays may reduce the clinical utility of this new biomarker routinely in APE [31,32]. The last limitation of the present study was having many exclusion criteria limiting generalizability.…”
Section: Limitations Of the Studymentioning
confidence: 97%
“…Furthermore, it may take more than 24 h to come back or it will have to be sent elsewhere to study this assay. These disadvantages of copeptin assays may reduce the clinical utility of this new biomarker routinely in APE [31,32]. The last limitation of the present study was having many exclusion criteria limiting generalizability.…”
Section: Limitations Of the Studymentioning
confidence: 97%
“…It has therefore been suggested that measurement of MPO may be useful for the early diagnosis of acute myocardial infarction. Collins et al (31) have been shown that the optimal timing for measurement of cardiac troponin remains to be defined and that additional measurements of myoglobin or CK-MB are not clinically effective or cost-effective in their study, completed with 850 patients. Highly sensitive cardiac troponins were evaluated at 0, 1, 2, 3, and 6 hours samples in a study.…”
Section: Discussionmentioning
confidence: 99%
“…troponins, creatinine kinase MB isoenzyme, and probably myoglobin) might no longer be the optimal early predictors in STEMI patients undergoing primary PCI, while they are able to depict worsening myocardial perfusion, myocardial infarct size, cardiac function and postponed left ventricular remodeling. Moreover, as a prognostic marker, CK-MB isoenzyme measured on admission was superior to cardiac troponin using a highsensitivity assay, NTpro-Brain Natriuretic Peptide (BNP) measurement on admission, but myoglobin, heart-type fatty acid-binding protein, copeptin and B-type natriuretic peptide were prognostically equivalent [12]. Consequently, to improve predictive approaches based on biomarker measurement in PCI patients, discovery of novel biomarkers maximally attributed solely to each individual after PCI is required.…”
Section: Introductionmentioning
confidence: 99%